Simplifying
m^{2} + 18m + 81 = 0
Reorder the terms:
81 + 18m + m^{2} = 0
Solving
81 + 18m + m^{2} = 0
Solving for variable 'm'.
Factor a trinomial.
(9 + m)(9 + m) = 0
#### Subproblem 1

Set the factor '(9 + m)' equal to zero and attempt to solve:
Simplifying
9 + m = 0
Solving
9 + m = 0
Move all terms containing m to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + m = 0 + -9
Combine like terms: 9 + -9 = 0
0 + m = 0 + -9
m = 0 + -9
Combine like terms: 0 + -9 = -9
m = -9
Simplifying
m = -9
#### Subproblem 2

Set the factor '(9 + m)' equal to zero and attempt to solve:
Simplifying
9 + m = 0
Solving
9 + m = 0
Move all terms containing m to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + m = 0 + -9
Combine like terms: 9 + -9 = 0
0 + m = 0 + -9
m = 0 + -9
Combine like terms: 0 + -9 = -9
m = -9
Simplifying
m = -9#### Solution

m = {-9, -9}